Formulation & evaluation of Myrrh toothpaste / Abd Majid N.H ... [et al.] - Abd Majid, N.H; Abdul Rahim, R.S; Younis, L.T; Abu Hassan, M.I (Faculty of Dentistry, Universiti Teknologi MARA, 2022)
Objectives: To formulate and measure the cytotoxicity level of organic myrrh toothpaste. Materials and Methods: Myrrh extract was prepared by the freeze drying process. Toothpaste was formulated by mixing specified amounts of myrrh extract, hydroxypropyl methylcellulose (HPMC) polymer, sodium lauryl sulphate (SLS), mint, and sucralose with deionized distilled water. MTT test was performed using concentrations of 100, 200, 300 and 400 mg/ml to assess the effect of myrrh paste on the gingival fibroblasts viability at intervals of 24 and 48hrs. The results were analysed by using SPSS version 27. Results: The formulated myrrh toothpaste has a homogeneous consistency as the extracted myrrh successfully dissolved completely with the other components. Cell viability test showed that myrrh paste concentrations of 100 - 300mg/ml were effective in maintaining the rate of fibroblasts growth after 24 and 48 hours as compared to the control samples. Cell growth rate was suppressed in the test samples treated with paste concentration of 400mg/ml. The results of the study imply that 300mg/ml is the safe and optimal concentration for fibroblasts growth, whereas concentrations ≥ 400mg/ml are intolerable and might be suppressing the proliferation of fibroblasts. Conclusion: Myrrh toothpaste concentration at 300mg/ml is the safe and optimal concentration for fibroblasts growth as depicted in the results, suggesting that at the optimal formulation, myrrh extract may not be toxic to the soft tissues and myrrh toothpaste may be useful for oral health care. Further clinical investigations are recommended to obtain the clinical efficacy data of the organic myrrh toothpaste.